Changes in the spectrum of kidney diseases: a 14-year single-center retrospective renal biopsy study from southeast China - Zishan Lin; Shidong Xie; Wenfeng Wang; Tao Hong; Bingjing Jiang; Caiming Chen; Xuan Tao; Dewen Jiang; Jianxin Wan; Hong Chen; Yanfang Xu (PeerJ)
Objective Kidney disease has become a significant public health issue. Socioeconomic improvements and environmental changes in China have influenced the kidney disease spectrum. This study aims to examine the changing spectrum of biopsy-confirmed kidney diseases in a single center from southeastern China and explore their clinical-pathological correlations. Methods Patients who underwent renal biopsy at the First Affiliated Hospital of Fujian Medical University from January 2010 to December 2023 were included in this retrospective study. Clinicopathological data were collected and analyzed. Results 2,832 patients were enrolled. Primary glomerular diseases accounted for the majority of kidney diseases (69.0%), followed by secondary glomerular diseases, tubulointerstitial diseases, and others. Among primary glomerular diseases, membranous nephropathy (MN) was the most prevalent (34.9%), followed closely by IgA nephropathy (IgAN) (34.5%) and minimal change disease (18.5%), with an increasing trend for MN. For secondary glomerular diseases, lupus nephritis (34.3%), diabetic nephropathy (DN) (24.8%), and hepatitis B virus-associated nephropathy (HBVN) (9.0%) were the most common. HBVN showed a significant decrease, while DN increased annually. Nephrotic syndrome (NS) was the most frequent indication for renal biopsy (40.3%), followed by progressive chronic kidney disease (22.4%). MN (47.2%) was the leading pathology in NS, and IgAN (51.6%) was predominant in patients with proteinuria and hematuria. Conclusions The spectrum of kidney disease has changed within the last 14 years. The relative frequency of MN and DN increased significantly, while that of HBVN decreased significantly. These findings highlight the need for ongoing public health efforts tailored to the changing spectrum of kidney diseases.